Competitive Revenue Management (Rm.) Strategies of Five Star Hotels: A Case From Istanbul - Tevfik Demirciftci; Sahin Osmanoglu (Journal of Economy Culture and Society)
In today’s competitive world, the primary goal of hotels is to generate sustainable profitability. In order to achieve this goal, businesses are required to develop well-designed strategies and policies. Every vacant hotel room leads to a direct loss for the company. Therefore, because of the fixed capacity, capacity utilization and pricing is extremely important for hotels. This study explains the competitive revenue management (RM) practices of 5-star hotels in Istanbul. It investigates how hotels track their competitors, their strategies to gain a competitive advantage, and what factors they consider when determining their prices. The research employed a questionnaire containing pre-prepared RM-related inquiries administered to hotel RM department managers. Additionally, a situation assessment was conducted, drawing insights from the information provided by these managers. This study discovered that every revenue manager involved takes the competition seriously. Revenue managers consider competition to be obtaining the largest share of the available market share. This research anticipates that revenue management will extend its influence beyond room revenue and evolve into a more strategic department. The study underscores the importance of enhancing education and raising awareness about RM to address this gap effectively.